The government of nature - Weaver, Afaa M. (Afaa Michael), 1951- (Pitt poetry series., 2013)
This is the second volume of a trilogy (the first was The Plum Flower Dance) in which the poet analyzes his life, striving to become the ideal poet. He explores the trauma of his childhood - including sexual abuse - using a "cartography and thematic structure drawn from Chinese spiritualism." The poet is a practitioner of Daoism, and this collection deals directly with the abuse in the context of Daoist renderings of nature as metaphor for the human body.